Exploring Sexual Behaviour and Associated Factors among Adolescents in Saudi Arabia: A Call to End Ignorance - Ali Saad R. Alsubaie (Springer, 2019)
Little is known about sexual behaviour, attitudes, and associated factors among adolescents in Saudi Arabia. A cross-sectional study using a multistage sampling technique was conducted among 453 male adolescents selected from high schools in Riyadh, Saudi Arabia. About 54.1% of the adolescents practiced masturbation daily and 38% had experienced sexual contact, while 67% had friends who had experienced sexual contact. The majority of adolescents (72.2%) believed men engage in sexual experience before marriage, and only 11.5% discussed sexual health issues with their parents. Most adolescents believed in the effectiveness of sex education (92.3%) and the need for school-based sex education (85.6%). The logistic regression analyses showed adolescent sexual activity was independently associated with age [adjusted odds ratio (AOR) = 1.5, 95% confidence interval (CI): 1.3-1.8, p < 0.001), daily masturbation (AOR = 2.1, 95% CI: 1.3-3.2, p < 0.004), friends who engaged in sexual activity (AOR = 2.8, 95% CI: 1.4-4.6, p < 0.001), and belief that men experience sexual contact before marriage (AOR = 5.1, 95% CI: 2.8-9.3, p < 0.001). The findings indicated that male adolescents had negative attitudes toward sexual activity and were involved in risky sexual behaviour. To mitigate these issues, schools and community networks should be involved in the delivery of a culturally sensitive sexual health-promoting programme.